Dynamic simulation of performance development: prediction and optimal scheduling - Perl, J. (International Journal of Computer Science in Sport, 2005)
Development of performance output depends on load input in complex ways. Two central aims of training and performance analysis are optimizing the training effort and predicting the training result. The Performance Potential Metamodel PerPot models the interaction between training input and performance output in adaptive physiologic processes by means of antagonistic dynamics. This means that training input causes two concurrent effects - namely the performance improving response flow and the performance reducing strain flow. Depending on the respective delays with which these flows become effective, a training input can cause positive or negative results in the initial phase. In the phase of calibration those delay values have to be deduced from the original load and performance profiles. Once calculated, the delay values not only allow for simulating given performance values but also for predicting future ones. As will be demonstrated, prediction works surprisingly well and therefore can be used for developing optimal schedules. Moreover, comparing different schedules can help for understanding how the performance output changes if the load profile is changed. Doing this by means of simulation saves time and is careful with the athlete.